2010
DOI: 10.1016/j.jhazmat.2010.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals using a brewer's yeast strain of Saccharomyces cerevisiae: Chemical speciation as a tool in the prediction and improving of treatment efficiency of real electroplating effluents

Abstract: In the present work, the influence of the competitive effect of inorganic ligands (carbonates, chlorides, fluorides, phosphates, nitrates and sulphates), which can be present in real multi-metal electroplating effluents, on the biosorption of chromium, copper, nickel and zinc ions by yeast cells of Saccharomyces cerevisiae was rationally examined. Additionally, chemical speciation studies allowed optimizing the amount of yeast biomass to be used in the treatment of effluents contaminated with nickel. The appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 37 publications
0
49
1
Order By: Relevance
“…Other metals such as iron and nickel were also present (Machado et al, 2011). The organic load of both the effluent was very low (Machado et al, 2010(Machado et al, , 2011Javaid et al, 2011). The analysis of electroplating effluent is revealed that it contained comparatively higher concentrations of Cu (II) than CETP effluent.…”
Section: Results and Discussion Characterization Of Effluentsmentioning
confidence: 97%
“…Other metals such as iron and nickel were also present (Machado et al, 2011). The organic load of both the effluent was very low (Machado et al, 2010(Machado et al, , 2011Javaid et al, 2011). The analysis of electroplating effluent is revealed that it contained comparatively higher concentrations of Cu (II) than CETP effluent.…”
Section: Results and Discussion Characterization Of Effluentsmentioning
confidence: 97%
“…Industrial effluents can present organic (such as EDTA) and/or inorganic ligands (carbonates, chlorides, fluorides, phos-phates, nitrates, and sulphates) (Naja and Volesky 2010b); these ligands can also affect species distribution through complexa-tion, which reduces metal availability to be removed by yeast cells (Machado et al 2010a). It has been shown that the presence of fluorides, affected, deeply, Cr removal in an indus-trial effluent containing Cr(III), Cu(II), and Ni(II).…”
Section: Bioremediation Of Real Industrial Effluentsmentioning
confidence: 99%
“…the free and labile metal will be removed by yeast cells (Hughes and Poole 1991; a removal of 29 and 32 % of Sn and Cr, respectively, was described (van Wyk 2011). An efficient treatment of an real electroplating effluent containing nickel using flocculent brewing heat-inactivated biomass was described by Machado et al (2010a).…”
Section: Bioremediation Of Real Industrial Effluentsmentioning
confidence: 99%
“…One includes those essential for life, generally incorporated into enzymes and cofactors, but which become toxic in higher doses by militantly binding to enzymes and DNA and production of oxygen radicals via Fenton reaction (e.g., Fe, Zn, Cu, Mn,Co, Ni, Cr) The non essential metals are always toxic even in low concentrations (e.g., Hg, Cd, Pb) (Valls and Lorenzo, 2002). Presence of high concentrations of these heavy metals can directly affect the soil fertility and cause serious ecological problems, affecting the food chain, as well as exposing humans to health risks (Machado et al, 2010). Removal of these heavy metals from the environment using physicochemical processes is expensive, requiring a lot of energy and material, so that resorting to biological means, like the use of microorganisms offers an efficient substitute.…”
Section: Actinobacteria and Metalsmentioning
confidence: 99%